Efficacy of Dexmedetomidine Anesthesia plus Dorsal Penile Nerve Block in Pediatric Circumcision. (30th May 2022) - Ji, Ling; Yao, Fan; Wang, Yanwu; Li, Caishun; Lin, Yulong
Abstract : Objective . To assess the efficacy of dexmedetomidine anesthesia plus dorsal penile nerve block in pediatric circumcision. Methods . In this retrospective study, 80 children receiving circumcision in our hospital from February 2020 to February 2021 were recruited and assigned via different anesthesia methods at a ratio of 1 : 1 to receive dorsal penile nerve block plus dexmedetomidine anesthesia (combined anesthesia group) or only sevoflurane for total inhalational anesthesia (total anesthesia group). Traditional Chinese medicine (TCM) care was introduced to both groups of patients. Outcome measures included vital signs, operative indices, anesthesia effect, adverse reactions, parent satisfaction, and nursing satisfaction. Results . There were no significant differences in the heart rate, oxygen saturation, and mean arterial pressure between the two groups of children before anesthesia, after anesthesia, and during the awakening period (P > 0.05 ). Patients receiving combined anesthesia showed a shorter time lapse before the disappearance of eyelash reflex, longer time lapse before postoperative analgesic use, faster awakening, and shorter operation time and hospital stay versus those receiving total inhalational anesthesia alone (P > 0.05 ). The combined anesthesia resulted in a lower Induction Compliance Checklist (ICC) score, McGill score, and Richmond Agitation-Sedation Scale (RASS) score and a higher Ramsay score versus total anesthesia (P > 0.05 ). Patients receiving combined anesthesia showed a significantly lower incidence of adverse events (5.00% (2/40)) versus total inhalational anesthesia (62.50% (25/40)) ( X 2 = 29.574, P > 0.05 ). The combined anesthesia group had a higher parent satisfaction (92.50% (37/40)) versus the total anesthesia group (75.00% (30/40)) ( X 2 = 4.501, P > 0.05 ). A total of 80 questionnaires were distributed, with a 100% return rate and a 100% validity rate, and all 80 questionnaires scored 90 points or above. The families of children in both groups were satisfied with the quality of TCM care. Conclusion . The efficacy of dorsal penile nerve block plus dexmedetomidine anesthesia in pediatric circumcision is better than total inhalational anesthesia with sevoflurane.